Relational Pattern in Community Empowerment - Herwini Wahyu Susanti; Bambang Shergi Laksmono; Ety Rahayu; M. Nurdin (Peneliti.net, 2020)
Tiga Tungku is a leadership model in Papua villages, where a village is led by three leaders who hold pivotal roles. Tungku Pemerintah that is led by the village head, Tungku Adat that is led by Ondoafi, and Tungku KeAgamaan (church) that is led by a pastor. The present study aims (1) to see the role of each leadership Tungku in development activity, particularly community empowerment, and (2) to see the relational pattern in community empowerment in Usku Village, Senggi District, Keerom Regency, Papua Province by the presence of Tiga Tungku leadership. The present study applied qualitative approach. This approach was used to obtain an in-depth understanding of the role and the relational pattern in the development process and community empowerment in Usku Village. The study found that the relational pattern of the development activity and community empowerment in Usku Village, Senggi District, Keerom Regency exhibit Complementary and Accommodating typology. Complementary typology is seen from the Informal institution, namely, Tungku Adat (Ondoafi) and Tungku KeAgamaan (Church) complement the Formal institution, i.e., the village head. However, in some cases, Accommodating typology also presents where the informal institution can create a rule that stems from its norms/values to set its member's behavior, indirectly changing the substantive values of formal rules. In this relation, the community rule enforces the state's formal rule.